Ensuring the ethical application of user data in IoE-Driven E-commerce: A systematic review with proposed framework - Myint, Yin Lei Yee; Thinakaran, Rajermani; Paliyanny, Hushalictmy; Naing, Kaung Khant Yan; Kumargazhanova, Saule (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of the study is to propose a framework to ensure the ethical application of user data on the Internet of Everything (IoE) commercial platforms by investigating the ethical application of user data on IoE-driven e-commerce platforms, focusing on privacy challenges, regulatory impacts, and innovative privacy-preserving techniques. A systematic literature review (SLR) methodology was employed to analyze existing research on privacy challenges, regulatory frameworks, and technological solutions within IoE-driven e-commerce. The study synthesizes findings from 22 scholarly articles across multiple databases and proposes an Integrated Privacy-Compliance-Innovation (IPCI) Framework to harmonize ethical data use, regulatory compliance, and innovation. The research identifies three critical aspects of privacy in IoE-enabled e-commerce: (1) challenges arising from the integration of IoE technologies, such as data fragmentation and consent complexity; (2) regulatory measures like the General Data Protection Regulation (GDPR) that enforce stricter data protection standards that may hinder innovation; and (3) privacy-preserving approaches, including encryption protocols, blockchain-based systems, and privacy-by-design principles. The IPCI Framework integrates these elements into a cohesive model to address multifaceted privacy concerns while fostering technological innovation. The findings provide actionable insights for policymakers, researchers, and practitioners aiming to enhance trust and compliance in e-commerce ecosystems. The IPCI framework serves as a practical tool for organizations to implement robust privacy measures without compromising innovation. Future empirical testing of the framework across diverse e-commerce settings is recommended to validate its effectiveness. This study establishes a solid base that supports the alignment of innovation methods with user privacy standards in emerging e-commerce systems.